Computed Tomography Colonography Phantom: Construction, Validation and Literature Review - Lambert, Lukas (Iran J Radiol, 2016)
BACKGROUND: Several dedicated computed tomography (CT) colonography phantoms have been described previously. OBJECTIVES: To compare their pros and cons and describe the construction of a dedicated phantom that can be easily manufactured. MATERIALS AND METHODS: We found 15 different phantom designs by literature search and compared their advantages and disadvantages based on their description and images. We tested various materials for density and mechanical properties and constructed a phantom from polypropylene pipes (30 mm and 50 mm in diameter, 52 cm in length). Haustral folds were created by heat shaping and 39 intermediate sessile polyps with a target size of 6-10 mm and two flat lesions were created from silicone. Nine polyps were attached to a fold. The model was placed in a 30-cm barrel filled with water to simulate attenuation of human body. Attenuation of polyps was compared to intermediate polyps found in patients. RESULTS: None of the earlier colonic phantoms found in the literature incorporated all the properties that would ensure both reproducibility and validity of the model (including a rigid wall, density of the wall and polyps similar to human colon, at least two levels of distension and durability). In the present phantom, the average size of sessile polyps was 8.6 ± 0.9 mm and their density was 53 ± 24 HU. We found no significant difference in polyp density between simulated polyps in the phantom and polyps in human subjects (P = 0.70). All polyps, with the exception of one flat lesion, were detected by computer aided detection. CONCLUSION: We constructed and validated a CT colonography phantom with correct density allowing performance of reproducible experiments.